Palaeoenvironment and early human occupation of southernmost South America (South Patagonia, Argentina) - Mancini, Maria Virginia; Franco, Nora Viviana; Brook, George (Quaternary International)
Pollen and archaeological records from two areas of southern Patagonia, one in the southern part of the Deseado Massif, the other south of Lago Argentino, suggest an important influence of climate on human movements into new areas. Pollen spectra record a significant dry climate throughout the region prior to ca. 12,900 cal BP that may correlate with the Antarctic Cold Reversal (ACR) from ca. 14,500 to 12,700 cal BP. The earliest archaeological sites date the initial exploration (sensu Borrero, 1994e95) of the Deseado Massif between 13,081 and 12,141 cal BP at the time of the Northern Hemisphere Younger Dryas (YD) cold interval (ca. 12,700e11,500 cal BP), which in the Southern Hemisphere was a time of gradually increasing temperatures. When humans set foot into the Deseado Massif, vegetation was grass steppe,indicating that conditions were wetter than during the ACR. The area south of Lago Argentino was occupied somewhat later around 11,000 cal BP, also when the vegetation changed to grass steppe. As temperatures increased during the early Holocene, forest replaced grass steppe in southwest Santa Cruz. A mix of forest and grass steppe persisted until ca. 9400 cal BP, when there was a return to drierconditions as those of today in the Deseado Massif. Fil: Mancini, Maria Virginia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Mar del Plata. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Franco, Nora Viviana. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Saavedra 15. Instituto Multidisciplinario de Historia y Ciencias Humanas; Argentina Fil: Brook, George. University of Georgia; Estados Unidos